2020
DOI: 10.3390/pr8020231
|View full text |Cite
|
Sign up to set email alerts
|

Thermal–Hydraulic Performance in a Microchannel Heat Sink Equipped with Longitudinal Vortex Generators (LVGs) and Nanofluid

Abstract: In this study, the numerical conjugate heat transfer and hydraulic performance of nanofluids flow in a rectangular microchannel heat sink (RMCHS) with longitudinal vortex generators (LVGs) was investigated at different Reynolds numbers (200–1200). Three-dimensional simulations are performed on a microchannel heated by a constant temperature with five different configurations with different angles of attack for the LVGs under laminar flow conditions. The study uses five different nanofluid combinations of Al2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The results show that the time variations of Nussle number and friction factor are periodic with the same frequency as the rotation frequency of the vortex generator, and the amplitude of the Nussle number increases with the increase of the Reynolds number.Muallim et al [34] simulated the heat transfer characteristics of nanofluid flow in a microchannel with a longitudinal vortex generator at different Reynolds numbers, and the results showed that compared to the CuO-water nanofluid Al2O3-deionized water had the best heat transfer performance; CuO-PAO had the best heat transfer performance under the condition of different fluid base liquids, with Nussel's values ranging between 9.57 and 15.88 between 9.57 and 15.88. In addition, it was also found that the longitudinal vortex generator and nanofluid can effectively improve the overall heat transfer performance of the microchannel.Ali et al [35] used a single-phase model to numerically simulate the heat transfer process of the Al2O3-deionized water nanofluid flow in the heat exchanger of a parallel rectangular microchannel with different perturbation elements, and the results showed that the heat transfer performance of the microchannel with sawtooth fins was optimal when the volume fraction of particles was 3%, and the heating performance of the microchannel was better than that of parallel rectangular microchannel with different volume fraction of particles.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the time variations of Nussle number and friction factor are periodic with the same frequency as the rotation frequency of the vortex generator, and the amplitude of the Nussle number increases with the increase of the Reynolds number.Muallim et al [34] simulated the heat transfer characteristics of nanofluid flow in a microchannel with a longitudinal vortex generator at different Reynolds numbers, and the results showed that compared to the CuO-water nanofluid Al2O3-deionized water had the best heat transfer performance; CuO-PAO had the best heat transfer performance under the condition of different fluid base liquids, with Nussel's values ranging between 9.57 and 15.88 between 9.57 and 15.88. In addition, it was also found that the longitudinal vortex generator and nanofluid can effectively improve the overall heat transfer performance of the microchannel.Ali et al [35] used a single-phase model to numerically simulate the heat transfer process of the Al2O3-deionized water nanofluid flow in the heat exchanger of a parallel rectangular microchannel with different perturbation elements, and the results showed that the heat transfer performance of the microchannel with sawtooth fins was optimal when the volume fraction of particles was 3%, and the heating performance of the microchannel was better than that of parallel rectangular microchannel with different volume fraction of particles.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary flow enables the core flow to mix with the fluid near the wall to improve heat transfer efficiency. The cross-flow generated by the vortex can further reduce the thickness of the boundary layer (Saravanan et al, 2018;Al Muallim et al, 2020). The ribs on the side walls have a limited effect on the boundary layer of the flow channel, and the cooling performance is improved more significantly by the addition of ribs or vortex generator configuration at the bottom (Datta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%